Undergraduate EFL Students’ Perspective on Critical Reading - Rahmah Julianti; Sinta Dewi Anggung; Nur Ima (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study explores students' perspectives on critical reading, a crucial skill for academic success and intellectual development, focusing on fourth-semester undergraduates at STKIP YPUP Makassar. By analyzing their responses, the research identifies key factors influencing their engagement with critical reading practices. Although students reported a degree of confidence in their critical reading skills, they encountered significant challenges, including limited vocabulary, difficulty understanding complex texts, and inadequate resources. These findings highlight a disconnect between students' perceived abilities and their actual performance, suggesting that their confidence may not fully reflect their competencies in critical reading. The study underscores the need for improved teaching methods to address these challenges effectively. It suggests that educators should develop more targeted instructional strategies and provide additional resources to support students in overcoming their difficulties with critical reading. Given the students' reliance on teacher guidance, enhancing instructional practices is essential for helping them build stronger critical reading skills. The implications of these findings are significant for curriculum development and instructional practices in higher education, offering valuable insights for creating more effective approaches to foster critical reading skills and support students' academic success.